Polyethylenimine-Assisted Aggregation of β-Galactosidase from Kluyveromyces lactis - Nedim Albayrak; Rabia Akyol Kütük (Hittite Journal of Science and Engineering)

(untitled)
Using PEI as an aggregating agent with β-galactosidase from Kluyveromyces lactis was investigated with no solid support. PEI, a cationic polymer initiated instant aggregation with the enzyme in solution. The factors affecting the aggregation such as PEI to enzyme ratio, glutar aldehyde for cross-linking and pH were investigated. Aggregation and sedimentation as well as the residual activity of aggregates were effectively dependent on the PEI to enzyme ratios. Easily precipitating aggregates at the ratio of 1/8, PEI enzyme aggregates were able to contain all enzyme in the complexation and displayed 60% of initial lactase activity. The PEI aggregation of enzyme led to enhancements in chemical and physical characteristics compered to free enzyme. The soluble enzyme showed a narrow optimum at about pH 7 while pH optimum of the aggregates extended one pH unit toward the alkaline range. Upon overnight incubation at 40 ºC, aggregated enzyme displayed 30% greater stability on average at all pHs tested. Although the free enzyme showed the highest activity at 40°C, it rapidly lost 50% of its activity at 50°C. In contrast, the aggregated enzyme retained full activity at 50°C and 70% activity at 65°C. With markedly enhanced thermal stability, the half-life of the aggregated enzyme increased from 76 hours to 254 hours at 40ºC. Overall, the simple and rapid aggregation of PEI with the enzyme led to instant and intense clustering, resulting in higher thermal and pH stabilities. This method may potentially offer efficient and cost-effective catalysis in lactase conversion processes.